2015
DOI: 10.12688/f1000research.6587.1
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive imaging to monitor lupus nephritis and neuropsychiatric systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease that can affect multiple different organs, including the kidneys and central nervous system (CNS). Conventional radiological examinations in SLE patients include volumetric/ anatomical computed tomography (CT), magnetic resonance imaging (MRI) and ultrasound (US). The utility of these modalities is limited, however, due to the complexity of the disease. Furthermore, CT and MRI contrast agents are contraindicated in patients with renal impairment. Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…It allows nanoparticles to have a better chance to have contact with the surrounding tissues and cells, thus increasing the efficiency of cellular delivery [ 18 , 19 ]. Furthermore, systemically injected nanoparticles in vivo generally show enhanced accumulation to the pathological lesions found in tumors, hemorrhagic diseases, and inflammatory diseases [ 20 , 21 , 22 ]. These findings suggest that nanoparticles have ideal properties to be used as innovative carriers for drug delivery.…”
Section: Concept Of Targeted Delivery and In Vivo Behavior Of Nanomentioning
confidence: 99%
“…It allows nanoparticles to have a better chance to have contact with the surrounding tissues and cells, thus increasing the efficiency of cellular delivery [ 18 , 19 ]. Furthermore, systemically injected nanoparticles in vivo generally show enhanced accumulation to the pathological lesions found in tumors, hemorrhagic diseases, and inflammatory diseases [ 20 , 21 , 22 ]. These findings suggest that nanoparticles have ideal properties to be used as innovative carriers for drug delivery.…”
Section: Concept Of Targeted Delivery and In Vivo Behavior Of Nanomentioning
confidence: 99%
“…On the other hand, in a study comparing MRI with 11 C-PK11195 PET to identify joint inflammation in rheumatoid arthritis patients before clinical symptoms appeared (39), the latter method was found to be more predictive of the development of clinical flare than MRI. Finally, a study on imaging renal inflammation in animals and humans (40) showed that the use of 18 F-FDG PET and USPIO was generally able to identify regions of macrophage infiltration and its extent, especially in the setting of autoimmune diseases such as systemic lupus erythematosus and Sjögren syndrome.…”
Section: Imaging Of Inflammation At the Organ Levelmentioning
confidence: 99%